(untitled) (Annals of Medical Research, 2023)
Aim: Cancer stem cells (CSCs) are found in a wide range of cancers, and CD133 is one of the most commonly used markers for detecting CSCs. Compared to CD133⁻ populations in lung cancer, CD133⁺ cells are more capable of self-renewal, drug resistance and tumor initiation and demonstrate increased CSC capabilities. Though the anti-cancer activity of boric acid (BA) has been reported in relation to various cancers, there is no study showing its effect on CSCs. The aim of this study is to investigate the anti-cancer effects of BA in CD133⁺ CSCs and CD133⁻ cells from lung cancer cells. Materials and Methods: The H460 lung carcinoma cell strain was obtained from the American Type Culture Collection. CD133⁺ CSCs and CD133⁻ cells were separated using CD133 antibody conjugated to magnetic beads. The sphere formation assay (coated with SpheroMake) was used to assess the ability to maintain stemness. Cells were grown in serum-free RPMI1640 medium (with B27, N2 supplement, EGF and bFGF) to observe the development of spheres. To determine CD133 mRNA expression, total RNA was extracted and RT-qPCR was performed. The xCELLigence Real-Time Cellular Analysis (RTCA) system was used to determine the cytotoxic effects of BA. 25 mM, 12 mM, 6 mM, 3 mM, and 1 mM BA solutions were added to CD133⁺ CSCs and CD133⁻ cells. Results: The CD133⁺ CSCs composed approximately 1% of H460 cells. The mRNA expression of CD133 was 16 times higher in CD133⁺ CSCs cells than in CD133⁻ cells. CD133⁻ cells failed to form spheres but CD133⁺ CSCs did so, demonstrating CD133⁺ CSCs stemness characteristics. The xCELLigence RTCA system determined the IC50 doses of BA to be 6.7 mM and 5 mM for CD133⁺ CSCs and CD133⁻ cells. Conclusion: BA exhibited anti-cancer activity against the CD133⁺ CSCs and CD133⁻ cells. This study is the first to demonstrate BA’s anti-cancer effect on CSCs.